Integrated regulation of the cellular metabolism and function of immune cells in adipose tissue. (March 2016) - Oishi, Yumiko; Manabe, Ichiro
Summary: Obesity is known to associate with low‐grade, sustained, systemic inflammation, which is considered to be a key pathological basis for obesity‐associated diseases such as diabetes and atherosclerosis. Immune cells, including both lymphocytes and macrophages, play physiological and pathological roles in adipose tissue. They increasingly infiltrate obese adipose tissue as body weight is gained, after which the infiltrated cells promote adipose tissue inflammation and strongly impact systemic metabolism. Recent studies have shown that the immune and metabolic systems are highly integrated with one another. This recognition has provided new insight into the mechanisms of metabolic diseases. In addition to the link at the tissue level, studies have shown that immune cell function is coordinately regulated with cellular metabolism. This review summarizes the current understanding of the specific metabolic signatures adopted by lymphocytes and macrophages to mediate proper effecter function. These findings will be related to the regulation of adipose tissue homeostasis and inflammation.